Hereditary motor and sensory neuropathy-russe: New autosomal recessive neuropathy in balkan gypsies - Thomas, P. K.; Kalaydjieva, Luba; Youl, Brian; Rogers, Tamara; Angelicheva, Dora; King, Rosalind H. M.; Guergueltcheva, Velina; Colomer, Jaume; Lupu, Constantin; Corches, Axinia; Popa, Gabriela; Merlini, Luciano; et al. (Annals of neurology, 2001)
A novel peripheral neuropathy of autosomal recessive inheritance has been identified in Balkan Gypsies and termed hereditary motor and sensory neuropathy‐Russe (HMSN‐R). We investigated 21 affected individuals from 10 families. Distal lower limb weakness began between the ages of 8 and 16 years, upper limb involvement beginning between 10 and 43 years, with an average of 22 years. This progressive disorder led to severe weakness of the lower limbs, generalized in the oldest subject (aged 57 years), and marked distal upper limb weakness. Prominent distal sensory loss involved all modalities, resulting in neuropathic joint degeneration in two instances. All patients showed foot deformity, and most showed hand deformity. Motor nerve conduction velocity was moderately reduced in the upper limbs but unobtainable in the legs. Sensory nerve action potentials were absent. There was loss of larger myelinated nerve fibers and profuse regenerative activity in the sural nerve. HMSN‐R is a new form of autosomal recessive inherited HMSN caused by a single founder mutation in a 1Mb interval on chromosome 10q.